Definitions and treatment of oligometastatic oesophagogastric cancer according to multidisciplinary tumour boards in Europe. (March 2022) - Kroese, Tiuri E.; van Hillegersberg, Richard; Schoppmann, Sebastian; Deseyne, Pieter R.A.J.; Nafteux, Philippe; Obermannova, Radka; Nordsmark, Marianne; Pfeiffer, Per; Hawkins, Maria A.; Smyth, Elizabeth; Markar, Sheraz; Hanna, George B.; et al.
Abstract: Background: Consensus about the definition and treatment of oligometastatic oesophagogastric cancer is lacking. Objective: To assess the definition and treatment of oligometastatic oesophagogastric cancer across multidisciplinary tumour boards (MDTs) in Europe. Material and methods: European expert centers (n = 49) were requested to discuss 15 real-life cases in their MDT with at least a medical, surgical, and radiation oncologist present. The cases varied in terms of location and number of metastases, histology, timing of detection (i.e. synchronous versus metachronous), primary tumour treatment status, and response to systemic therapy. The primary outcome was the agreement in the definition of oligometastatic disease at diagnosis and after systemic therapy. The secondary outcome was the agreement in treatment strategies. Treatment strategies for oligometastatic disease were categorised into upfront local treatment (i.e. metastasectomy or stereotactic radiotherapy), systemic therapy followed by restaging to consider local treatment or systemic therapy alone. The agreement across MDTs was scored to be either absent/poor (<50%), fair (50%–75%), or consensus (≥75%). Results: A total of 47 MDTs across 16 countries fully discussed the cases (96%). Oligometastatic disease was considered in patients with 1–2 metastases in either the liver, lung, retroperitoneal lymph nodes, adrenal gland, soft tissue or bone (consensus). At follow-up, oligometastatic disease was considered after a median of 18 weeks of systemic therapy when no progression or progression in size only of the oligometastatic lesion(s) was seen (consensus). If at restaging after a median of 18 weeks of systemic therapy the number of lesions progressed, this was not considered as oligometastatic disease (fair agreement). There was no consensus on treatment strategies for oligometastatic disease. Conclusion: A broad consensus on definitions of oligometastatic oesophagogastric cancer was found among MDTs of oesophagogastric cancer expert centres in Europe. However, high practice variability in treatment strategies exists. Graphical abstract: Image 1 Highlights: 47 tumour boards of cancer expert centers discussed 15 real-life clinical cases. A consensus on definitions of oligometastatic oesophagogastric cancer was found. However, high practice variability in treatment strategies exists. This practice variability could potentially impact on quality of care.